Reduced quality of life in myasthenia gravis patients: A study on 185 patients from China - Wu, Xuan; Li, Run Yun; Ye, Xiao Bin; Wang, Ning (Frontiers in Neurology, 2023)
Aims: To explore the quality of life (QOL) in patients with myasthenia gravis (MG) and factors associated with QOL. Methods: This observational study included MG patients diagnosed at the First Affiliated Hospital of Fujian Medical University between January 2020 and March 2022. QOL of patients was evaluated with the 15-item Myasthenia Gravis Quality of Life (MG-QOL15). Results: One-hundred-and-eighty-five patients (72 males [38.9%], aged 45.2 years [14-77]) with MG were enrolled. Age at onset was 38.3±17.9 years, disease duration was 87.9 months (0-672). The median MG-QOL15 score was 12.5 (0-58). The item “have trouble using my eyes” was the highest scoring item in both ocular and generalized MG patients. The MG-QOL15 score was significantly different among patients with OMG (9.2±9.4, n=63), GMG (9.0±8.8, n=22), and BMG (15.4±14.2, n=100)(P=0.018). BMG patients had higher MG-QOL15 score than OMG (P=0.001) and GMG (P=0.009), but there was no significantly difference among OMG and GMG (P=0.467). The MG-QOL15 score was significantly lower in patients who had undergone thymectomy (9.7±9.8, n=58) compared to those who had not (13.8±13.4, n=127, P=0.022). MG-QOL15 score was significantly lower in patients who underwent thymectomy compared to those who did not (9.7±9.8, n=58 vs. 13.8±13.4, n=127, P=0.022). MG-QOL15 score was different among MGFA grades. There was no significantly difference between patients in MGFA grade I and II (P=0.896), and there was no significantly difference between patients in MGFA grade III and IVa (P=0.052). MG-ADL (P<0.001), and MGC (P<0.001) were positively correlated with MG-QOL15. Males had higher MG-QOL15 than female (P=0.094) and LOMG had higher MG-QOL15 than EOMG (P=0.072). Multivariate linear regression identified higher MG-ADL (P<0.001), higher MGC (P = 0.02), and poor employment status (P=0.045) were independent associated with higher MG-QOL15. Conclusion: Have trouble using eyes accounted for the highest score in MG-QOL15, eyes symptoms affect QOL more than limb weakness in MG. Daily life activity, disease severity, and employment status were associated with patients’ QOL. Adequate treatment should be applied to improve QOL, while mild symptoms can be accepted. The males and patients over the age of 50 years of onset may need more attentions.